Resiliensi Kawasan Permukiman Desa Pacarejo, Semanu, Kabupaten Gunung Kidul Terhadap Bencana Alam Puting Beliung - Aris Nur Lestarianto; Paulus Bawole; Freddy Marihot Rotua Nainggolan (ATRIUM: Jurnal Arsitektur, 2023)
Title: Resilience of the Settlement Area of Pacarejo Village, Semanu, Gunung Kidul Regency Against the Natural Disaster of Tornado   Natural disaster is a natural phenomenon often faced in several countries, including Indonesia, which has a variety of potential disasters. Pacarejo Village is an area in the Kapanewon Semanu, Gunung Kidul Regency, Daerah Istimewa Yogyakarta, which often experiences natural disasters. One of the natural disasters that often occurs in this region is the natural disaster of tornadoes. In this area, tornadoes have occurred several times, and on February 22, 2022, this disaster caused damage to residential areas, both houses and their surrounding environment. On the one hand, tornado disasters hurt people's lives, but on the other hand, they can also generate resilience in residential areas. This resilience makes the residential area in Pacarejo Village resistant and resilient to tornado disasters. This research aims to find out how the resident areas in Pacarejo Village are resilient to tornado disasters. The research method used is a qualitative method, which requires a narrative to explain the research systematically and accurately according to existing facts and data. The results of this research will show and provide lessons on how the resilience of the residential area formed in the Pacarejo District can face tornado disasters.